Association Between Diabetic Peripheral Neuropathy and Risk of Falls in Adults with Type 2 Diabetes: A Narrative Review - Ahmed, Faisal Wali; Mahato, Aakash; Mahmood, Jawad; Akram, Mahnoor; Basra, Abdullah Amir; Fatima Tuz Zahra; Cheema, Muhammad Usairam; Taticherala, Neelesh; Rehman, Maleeha; Hassan, Zohaib (Indus Journal of Bioscience Research, 2025)
Background: Diabetic peripheral neuropathy (DPN) is a prevalent and debilitating complication of type 2 diabetes mellitus (T2DM), characterized by progressive sensory and motor deficits. These impairments significantly increase the risk of falls, which are a major cause of injury, disability, and reduced quality of life in this population. Objective: This narrative review aims to synthesize current clinical evidence on the association between DPN and fall risk, identify key mechanisms contributing to instability, and highlight tools and strategies for fall prevention. Key Findings: DPN contributes to falls through multiple pathways, including sensory loss, proprioceptive dysfunction, gait abnormalities, postural instability, and neuropathic pain. Clinical studies confirm a significantly higher fall incidence in individuals with DPN compared to diabetic patients without neuropathy. Validated tools such as the monofilament test, vibration perception threshold, and Timed Up and Go (TUG) test are effective in assessing fall risk. Preventive strategies including glycemic control, balance training, foot care, and assistive devices show promise but are underutilized. Limitations in current literature include reliance on cross-sectional designs, inconsistent definitions, and lack of inclusive or long-term data. Conclusion: DPN is a critical yet under-addressed risk factor for falls in adults with T2DM. Routine fall risk screening and comprehensive, multidisciplinary management approaches should be integrated into diabetic care to reduce fall-related morbidity and improve functional outcomes.